Model-based inference on the impact of early access to antiretroviral therapy to all on HIV incidence among adolescent girls and young women in Eswatini - Chibawara, Trust (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2021.